Improving the attendance management of the employees of UltraShip Crewing Phils., Inc. - Miranda, Jaemee Anne S. (Animo Repository, 2018)
This action research focuses on improving the attendance management system of a crew management company in Manila, Philippines. By changing the way, the company has been doing the process through revision of the existing attendance procedures in the company Quality Management System, implementing an HR System and door access system, the company now has a better overview of the attendance of the employees. The success of the implementation of the intervention can be attributed to the use of Jeff Hiatt’s ADKAR Model of change management and Victor Vroom’s Expectancy Theory because these provided guidance on how to carry out the change needed in the organization. Having systems in place helped in fostering discipline and encouraged employees to be responsible of their attendance which previously, was managed manually.